2020
DOI: 10.1002/jcph.1677
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Aided Adults‐to‐Children Pharmacokinetic Extrapolation and Empirical Body Size‐Based Dosing Exploration for Therapeutic Monoclonal Antibodies—Is Allometry a Reasonable Choice?

Abstract: The importance of pharmacokinetic (PK) evaluation in pediatric drug development is well recognized, and a pediatric PK study is generally recommended before pivotal trials to ensure the "right" dose in these studies. The PK of therapeutic monoclonal antibodies (mAbs) is primarily affected by body weight, where adults-to-children extrapolation may conform to allometry. Therefore, PK behavior of mAbs in pediatrics, particularly for those with linear PK, is expected to be predictable based on data in adults. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 26 publications
(61 reference statements)
2
37
1
Order By: Relevance
“…The consequence is that terminal elimination half‐life can be the similar between adults and children, but overall concentrations are lower for an intravenously administered therapeutic protein with weight‐normalized dosing. These observations are in agreement with similar results reported specifically for mAbs 45 . A consistent pattern of exposure was observed for all therapeutic proteins in this study, regardless of size or affinity for the neonatal Fc receptor (FcRn).…”
Section: Observations On Pediatric Exposuresupporting
confidence: 93%
See 2 more Smart Citations
“…The consequence is that terminal elimination half‐life can be the similar between adults and children, but overall concentrations are lower for an intravenously administered therapeutic protein with weight‐normalized dosing. These observations are in agreement with similar results reported specifically for mAbs 45 . A consistent pattern of exposure was observed for all therapeutic proteins in this study, regardless of size or affinity for the neonatal Fc receptor (FcRn).…”
Section: Observations On Pediatric Exposuresupporting
confidence: 93%
“…Deviating from conventional allometry, our review finds that exponents between 0.7 and 1.0 are most frequently applied for describing the effect of body weight on volume of distribution for therapeutic proteins in children (median, 0.81). Similarly, but specific to mAbs, a recent review also noted allometric exponents between 0.7 and 0.9 in 20 popPK models for children, although the authors cautioned that their results may have been confounded by poor sampling schemes 45 . The allometric exponent of 0.8 for volume of distribution has physiologic relevance, as it reflects that young children have higher extracellular water fractions than adults 57,58 .…”
Section: First‐in‐pediatric Dose Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allometric scaling is an old but powerful tool for scaling doses for pediatric patients 17 . While early investigations in the pediatric population suggested that older pediatric populations were more appropriate for scaling doses from adults, 18 more recent evaluations have suggested that allometric scaling can be used for neonates and infants, 19–21 for obese pediatric patients, 22 and for therapeutic protein doses in pediatric patients 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Information on dosing in obese pediatric patients is not available in FDA‐approved labels, 42 and yet allometry may provide a method of estimating drug clearance in obesity 43 . Therapeutic monoclonal antibodies that are approved for pediatric use have widely divergent dosing recommendations, 44 but allometry has been suggested as being a reasonable approach for dosing in older children 45 . The use of allometry to predict DDI 46 and to predict drug clearance in extremely low‐birth‐weight infants 47 are additional applications that have been proposed for drug development.…”
Section: Application Of Modeling In Pediatric Dosing Developmentmentioning
confidence: 99%